2021
DOI: 10.1039/d0ta10564c
|View full text |Cite
|
Sign up to set email alerts
|

Efficient spatial charge separation in unique 2D tandem heterojunction CdxZn1−xIn2S4–CdS–MoS2 rendering highly-promoted visible-light-induced H2 generation

Abstract: Unique 2D heterostructures CdxZn1−xIn2S4–CdS–MoS2 with effective charge separation, excellent light-harvest, and abundant active sites are highly-efficient for photocatalytic H2 evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…This finding demonstrates that the oxidation of Ti 3 C 2 T x that has retained its conductive nature should be moderate. 46…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding demonstrates that the oxidation of Ti 3 C 2 T x that has retained its conductive nature should be moderate. 46…”
Section: Resultsmentioning
confidence: 99%
“…This nding demonstrates that the oxidation of Ti 3 C 2 T x that has retained its conductive nature should be moderate. 46 So far, we focus on the impedance spectroscopy technique which provides insights into the characterization of the electrical properties of the materials. [47][48][49] The impedance test of the sample lm was performed in an air atmosphere, as reported by Bobkov et al 48 Fig.…”
Section: àmentioning
confidence: 99%
“…156 Many studies have examined the impact of vacancies on the HER performance of MoS 2 . 157–167 Theoretically, the rational design of defects on the basal plane of MoS 2 can enhance the HER performance of MoS 2 because the basal plane of MoS 2 is inert while the edge sites are significantly more active.…”
Section: Main Strategies To Promote the Her Performance Of Mos2mentioning
confidence: 99%
“…By using Ni 2 P as a cocatalyst, composite ZnIn 2 S 4 /Ni 2 P heterostructures displayed an enhanced H 2 evolution rate of 2.066 mmol h −1 g −1 compared to pure ZnIn 2 S 4 , but it is still far from meeting the criteria for practical application. 28 Our recent study indicated that 29 the HER performance of ZnIn 2 S 4 could be enhanced by Cd-doping to achieve light responsive characteristics. Therefore, 2D hierarchitectures based on Cd-doped ZnIn 2 S 4 coupled with graphene and Ni 2 P are expected to possess excellent performance towards visible-light-driven H 2 production.…”
Section: Introductionmentioning
confidence: 99%